Slick scripts: impact on patient flow targets of pharmacists preparing discharge prescriptions in a hospital with an electronic prescribing system. Issue 2 (15th August 2016) - Tran, Tim; Hardidge, Andrew; Heland, Melodie; Taylor, Simone E; Garrett, Kent; Mitri, Elise; Elliott, Rohan A
Abstract: Rationale, aims and objectives: Inpatient bed access decreases when ward discharge is delayed. This contributes to prolonged emergency department (ED) length of stay (LOS) which has been associated with increased hospital LOS and mortality. Delays in preparation of discharge medication prescriptions by ward doctors may contribute to delayed ward discharge. This project aimed to evaluate the effect on patient flow of having a pharmacist collaborate with ward doctors to prepare discharge prescriptions at a hospital with an electronic prescribing system. Method: Eight‐week pre‐ and post‐intervention study on two surgical wards at a major metropolitan Australian hospital. During the intervention, a project pharmacist (PP) electronically prepared discharge prescriptions, in consultation with ward doctors, which were reviewed by the regular ward pharmacist before being dispensed. Outcome measures, based on hospital performance indicators, included: Percentage of patients transferred to wards from ED within four and six hours of presentation; Median time (minutes) past 9 am that patients were discharged from the wards; Percentage of patients discharged from wards by 9 am; Staff satisfaction. Results: Pre‐ and post‐intervention, there were 259 and 246 patients transferred from ED to the study wards, respectively. The percentage of patients transferred within four and six hours of presentation did not change. There were 320 and 341 patients discharged, pre‐ and post‐intervention, respectively, who required a discharge prescription. The PP prepared 273 (80%) prescriptions during the post‐intervention period. Patients were discharged 57 minutes earlier with the intervention (median 211 vs. 154 minutes past 9 am, P  = 0.01). The percentage of patients discharged before 9 am increased from 6% to 12% ( P  = 0.01). All 26 health‐professional respondents (79% response rate) were satisfied with the service and recommended its continuation. Conclusions: Pharmacist collaboration with doctors to prepare discharge prescriptions did not impact upon ED access targets, but resulted in patients being discharged earlier.